A Review on the Irrational Use of Medicines - Habibyar, Ahmad Farid (Journal of Natural Sciences – Kabul University, 2022)
Medicines are an integral part of healthcare delivery systems. However, they are expensive commodities and account for a significant proportion of overall health expenditure in most countries. The irrational use of medicines is a major challenge faced by many health systems worldwide. Unfortunately, more than 50% of medications are prescribed, dispensed, and sold irrationally. Additionally, over 50% of patients do not use their medications correctly. The aim of this study is to review the issue of irrational medicine use, based on a comprehensive review of credible scientific literature. The study concludes that irrational use of medicines persists in many countries, including Afghanistan. Fortunately, some measures have been adopted to address this problem. However, due to the widespread nature of the issue, these actions are insufficient, and more comprehensive efforts are required to tackle the problem effectively.